2014
DOI: 10.3390/f5092163
|View full text |Cite
|
Sign up to set email alerts
|

Legal Harvesting, Sustainable Sourcing and Cascaded Use of Wood for Bioenergy: Their Coverage through Existing Certification Frameworks for Sustainable Forest Management

Abstract: Abstract:The first objective of this paper was to provide an inventory of developments of certification schemes for sustainable biomass production, following recent EU legislation (both formalized and under development). One main pillar is the EU Timber Regulation for legal harvesting; a second one is the EU's 2010 recommendations for sustainable woody biomass sourcing for energy; the third one is the EU Waste Directive. The second objective was to benchmark the coverage of this (draft) legislation, when wood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 38 publications
0
40
0
1
Order By: Relevance
“…Therefore, the waste hierarchy elements -prevention and preparing for reuse, recycling, recovery, and disposal -are also included as criteria. Another argument for including the waste hierarchy elements is because the cascading principle is already included in the waste hierarchy to some extent when it refers to prioritizing the reuse of waste materials [28,29]. The 3Rs as well as the waste hierarchy elements are defined in Table 2 according to the European Union descriptions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the waste hierarchy elements -prevention and preparing for reuse, recycling, recovery, and disposal -are also included as criteria. Another argument for including the waste hierarchy elements is because the cascading principle is already included in the waste hierarchy to some extent when it refers to prioritizing the reuse of waste materials [28,29]. The 3Rs as well as the waste hierarchy elements are defined in Table 2 according to the European Union descriptions [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comparison of existing SFM certification schemes with the UK Category A and B evidence requirements, Sikkema et al (2014a) showed that many schemes already comply with most (but not all) requirements (Table 8.6). The GHG emission savings calculations, required by the UK Category A and B evidence requirements, are not adequately addressed by many pre-existing SFM certification schemes.…”
Section: The United Kingdommentioning
confidence: 99%
“…All developed their own verification system for sustainable biomass, like, for example, the Green Gold Label developed by Essent [3]. Other major energy utilities headquartered or operating in the Baltic Sea Region like E.ON [53], DONG Energy [48], FORTUM [54] and Vattenfall [55] endorsed own biomass procurement principles, guidelines and policies.…”
Section: Sustainable Biomass Procurement Policies Of Energy Utilitiesmentioning
confidence: 99%
“…Article 194 of the Treaty on the Functioning of the European Union (TFEU) 3 contains four objectives of European energy policy. Hence, Union policy on energy shall aim, in a spirit of solidarity between Member States, to:…”
Section: Eu Policy Framework Addressing Sustainability Of Bioenergymentioning
confidence: 99%
See 1 more Smart Citation